Body Gesture Based Gaming, Math Solving and Mouse Controlling - Mr. Manish Mahajan, Dr. Lokendra Singh Songare (Journal of Neonatal Surgery, 2025)
The advancement of machine learning and computer vision technologies has surged, which enabled the idea behind the development of innovative gesture recognition systems that enhance human-computer interaction. "GenX: Move. Play. Solve." is an instigating project that leads to scope in gesture recognition technique to monitor & control the devices and applications through natural hand and body movements. This project introduces a versatile system that is capable of performing three distinct tasks: ‘Mouse Controller, Game Controller, and Gesture Calculator’. Each module transforms user gestures into real-time, responsive actions, providing a seamless and intuitive user experience without the need for traditional input devices like keyboards or mouse. By applying modules for device control, gaming, and calculation, GenX aims to push the boundaries of gesture-based interaction and create new possibilities for accessibility, engagement, and productivity.